2020
DOI: 10.2533/chimia.2020.18
|View full text |Cite
|
Sign up to set email alerts
|

Cascades, Catalysis and Chiral Ligand Control with SmI2; The Rebirth of a Reagent

Abstract: This review focuses on recent developments from our laboratory in the field of radical reactions mediated by the archetypal reductive single electron transfer (SET) reagent, SmI2. Namely, we have expanded the scope of reducible carbonyl moieties to esters and amides and have exploited the resultant ketyl radicals in radical cascade reactions that generate unprecedented scaffolds. Moreover, we have taken the first steps to address the long-standing challenges of catalysis and chiral ligand control associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, the use of SmI 2 for ketyl radical formation has remained popular due to its versatility-a variety of carbonyl compounds can be converted to the corresponding ketyl radicals using the reagenttuneability, commercial availability, and ability to control the stereochemical course of subsequent radical couplings by coordination to Lewis basic sites in substrates. [10][11][12] In a classical approach, Cheng and co-workers reported the coupling of aryl/heteroaryl ketones and aldehydes 1 with a range of electron deficient alkenes 2, including acrylates, acrylamides, acrylonitriles, and vinyl sulfones, to furnish g-hydroxyl butyric acid derivatives 3 (Scheme 1). 13 Importantly, the reaction does not require strong single-electron reducing agents, such as alkali metals, and instead uses inexpensive Zn metal.…”
Section: Generation Of Ketyl Radicals Using Metals Pseudo-metals Andmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of SmI 2 for ketyl radical formation has remained popular due to its versatility-a variety of carbonyl compounds can be converted to the corresponding ketyl radicals using the reagenttuneability, commercial availability, and ability to control the stereochemical course of subsequent radical couplings by coordination to Lewis basic sites in substrates. [10][11][12] In a classical approach, Cheng and co-workers reported the coupling of aryl/heteroaryl ketones and aldehydes 1 with a range of electron deficient alkenes 2, including acrylates, acrylamides, acrylonitriles, and vinyl sulfones, to furnish g-hydroxyl butyric acid derivatives 3 (Scheme 1). 13 Importantly, the reaction does not require strong single-electron reducing agents, such as alkali metals, and instead uses inexpensive Zn metal.…”
Section: Generation Of Ketyl Radicals Using Metals Pseudo-metals Andmentioning
confidence: 99%
“…Recent studies have shown that this reagent system can also be used to generate unusual ketyl radical anions by SET reduction of the carbonyl groups in esters and amides. [10][11][12] Inorganic additives (e.g. LiCl, LiBr, NiCl 2 , and FeCl 3 ) and organic additives (e.g.…”
Section: Generation Of Ketyl Radicals Using Metals Pseudo-metals Andmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 In particular, cyclizations triggered by single electron transfer (SET) 2 reduction of carbonyl compounds, using the archetypal SET reducing agent samarium(II) diiodide (SmI 2 , Kagan’s reagent), 3 offer a radical umpolung strategy that couples carbonyl moieties with unsaturated functionalities and delivers decorated cyclic structures ( Scheme 1 A). 4 For example, the facile intramolecular addition of ketyl radicals, 5 generated upon treatment of ketones and aldehydes with SmI 2 , 6 to alkenes continues to provide effective solutions for the synthesis of high-profile natural products and bioactive molecules. 7 Recently, our group 8 and others 9 have exploited the use of coordinating additives (e.g., H 2 O, phosphoramides, ureas, amines, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide halides and halide complexes are widely used as starting materials for the syntheses of organolanthanide compounds, e.g., in salt metathesis and reduction , processes. Those of divalent lanthanides, most importantly SmI 2 , are widely utilized as powerful and selective reductants for various organic transformations. Knowing their exact structures is important for the following chemistry, not only for determining the stoichiometry in their reactions but also for understanding reactivity, magnetic interactions, and other properties, which depend on the local environment of the Ln cation. Multiple studies showed that the molecular structures of lanthanide halide complexes highly depend on the donor solvent used in the synthesis. , Coordination of small donor molecules mainly leads to mononuclear complexes.…”
Section: Introductionmentioning
confidence: 99%